Tunable photon transmission through a waveguide cavity coupled to an electron spin ensemble. (5th January 2017) - Feng, Zhi-Bo; Yan, Run-Ying; Yan, Lei-Lei; Zhou, Yun-Qing
Abstract: We propose an effective scheme for implementing tunable photon transmission through a coplanar waveguide cavity. An electron spin ensemble of nitrogen-vacancy centers, behaving as a spin-boson mode, is coupled to the cavity mode. It is found that the transmittance of an incident photon depends on the coupling strength between the two modes, both with dissipative effects. In particular, the photon transmittance can be controlled at will by adjusting the external driving-induced detunings. This proposal could offer a promising avenue to coherently control photon propagation and is highly preferable for the experimental manipulations.